A nanobrush-shearing strategy enabling the alignment of 1D nanomaterials for synchronous electrochromic actuators and controlled growth of neural stem cells. (December 2022) - Li, L.; Wu, C.; Ling, Y.; Hou, C.; Zhang, Q.; Li, Y.; Shi, H.; Wang, H.; Li, C.; Yin, S.
Abstract: Approaches to prepare ordered topographies have been stimulated by demands in the emerging fields of biological electronics, smart wearables, in which brush shearing technology (BST) is widely utilized due to the features of large-scale ability and facile operation. However, BST hardly realized the efficient processing of nanomaterials due to the size mismatch between microscale brush hairs and nanoscale brushed units. Herein, we explore a unique nanobrush-shearing technology (NBST) for the tailored assembly of nanomaterials through regulation of applied shear forces on the brushed units, in which films/yarns composed of parallel nanoscale building blocks are utilized as hydrophilic/oleophilic nanobrushes according to their wetting and dewetting capabilities. Aligned and cross-aligned morphologies are created via NBST and their proof-of-concept applications in electrochromic actuators and directional cell growth are demonstrated. Aligned vanadium pentoxide nanobelts achieve synchronous electrochemical actuation and electrochromism, triggered by the ion absorption and redox reactions in ionic liquid electrolyte. Aligned silver nanowires exhibit significantly directional influences on the growth of proliferating and differentiating neural stem cells, demonstrating the manipulating ability of NBST in nerve tissue regeneration. This work expresses notable advantages of NBST to realize tailored assembly of multiple nanomaterials for meeting the challenges in nano bioengineering and printed electronics, etc. Graphical abstract: A nanobrush-shearing strategy (NBST) is explored to promote the transfer of shear forces to the brushed units through nanobrushes that are composed of compacted and parallel nanohairs. Multiple 1D nanomaterials are aligned via NBST. Aligned vanadium pentoxide nanobelts achieve electrochemical actuation and electrochromism in electrolyte; aligned silver nanowires exhibit a controlled growing influence on proliferating and differentiating neural stem cells. Image 1 Highlights: Hydrophilic/oleophilic nanobrushes composed of parallel nanohairs are explored. Assembly of 1D nanomaterials is realized through a facile nanobrush-shearing process. A film of aligned V2 O5 nanobelts shows electrochemical actuating and electrochromism. Aligned Ag nanowires shows directional influences on the growth of neural stem cells.